RELC journal. - Regional English Language Centre; Regional Language Centre (London SAGE Publishing, 1969)
"RELC Journal is published on behalf of the Southeast Asian Ministers of Education Organisation (SEAMEO) Regional Language Centre (RELC), located in Singapore. It presents information and ideas on theories, research, methods and materials related to language learning and teaching."--Sage publisher site.
"An Internationally Refereed Journal of Language Teaching and Research."
Published: Singapore : Oxford University Press, 1970- ; SEAMEO Regional Language Centre, <1991>-2002; London : Continuum, 2003-Apr. 2004; Sage Publications, Aug. 2004-
UP System perpetual contents: 2019
Issued by: Regional English Language Centre, 1970-1976; by: Regional Language Centre, 1977-
Keywords: English language -- Research -- Southeast Asia -- Periodicals; English language -- Study and teaching -- Southeast Asia -- Periodicals; Language teaching; Second language; Languages (General).